The Effect of Combined Hypertrophy-Neural Training Methods and Neural Training Methods on The Improvement of Maximum Strength in The Lower Limbs of Muay Thai Athletes - Muhammad Raisya Septiana Putra; Berliana; Bambang Erawan; Ira Purnamasari (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Strength is very important for achieving optimal performance in sports, serving to develop other biomotor components. A lack of maximum strength will have an impact on the decline of biomotor components and increase the risk. The purpose of this study was to determine whether there was an effect of the combination of hypertrophy-neural training and neural training methods on the increase in maximum leg muscle strength in Muay Thai athletes. This study employed an experimental method with a quantitative approach, using a two-group pre-test post-test design. It involved 30 Muay Thai athletes at Ares Fighting Camp, and the sample selection used total sampling. The treatment consisted of 18 sessions at the beginning and end of the sample period, with a Leg Dynamometer test administered to determine the components of leg muscle strength in the sample. After the data was obtained, the Mann-Whitney hypothesis test yielded a statistical Sig value (2-tailed) of 0.360, which was greater than the probability value of 0.05. Therefore, it can be concluded that there was no difference in the effect of the combination of neural hypertrophy training and neural training methods on increasing the maximum leg muscle strength of Muay Thai athletes. It is recommended that coaches and athletes increase maximum leg muscle strength using the neural hypertrophy combination training method because it targets the desired physiological adaptation by combining two training phases: the hypertrophy phase to increase muscle volume/strength and the neural phase to increase nerve activation efficiency and compact the body so that strength can be increased while adding muscle volume.